Do teacher-training college students become more engaged in their studies because of commitment? The mediating role of self-control and the moderating role of core self-evaluation - Li, Chen (Frontiers in Psychology, 2025)
ObjectivesAs prospective educators, teacher candidates’ learning engagement and development require significant attention. This study aims to investigate the mechanism of the role between professional commitment and learning engagement of teacher-training college students.MethodsA questionnaire survey was conducted with 846 randomly sampled teacher-training college students using four validated scales: the College Student Professional Commitment Scale, the Self-Control Dual-System Scale, the Core Self-Esteem Scale, and the Learning Engagement Scale. The study employed descriptive statistics and structural equation modeling to validate the proposed measurement model and analyze the interconnections between the variables under investigation.ResultsThe results showed that (1) Different dimensions of professional commitment have significant effects on self-control; (2) Both the impulse and control systems of self-control significantly affect learning engagement; (3) The impulsive system and control system of self-control mediate the different dimensions of professional commitment; (4) The effect of the impulse system and control system of self-control on learning engagement is moderated by core self-evaluation.ConclusionThe study’s results reveal the mechanism of different dimensions of professional commitment’s influence on learning engagement, particularly the roles of self-control (including both impulsive and control systems) and the core self-evaluation. These findings provided valuable insights for designing intervention to enhance learning engagement among teacher education students.